High‐efficiency yellow light‐emitting diodes grown on sapphire (0001) substrates. Issue 3 (17th February 2014) - Hashimoto, Rei; Hwang, Jongil; Saito, Shinji; Nunoue, Shinya
Abstract: High‐efficiency yellow InGaN‐based light‐emitting diodes (LEDs) were grown by metal‐organic chemical vapor deposition on conventional c‐plane sapphire (0001) substrates. Optimization of the growth temperature of barrier layers eliminated surface inclusions and resulted in improved output properties of the fabricated yellow LEDs. They exhibited a high output power of 8.4 mW and external quantum efficiency of 19.3% for yellow light (570 nm) at an injection direct current of 20 mA. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)